PELAKSANAAN PASAL 25 AYAT (1) PERATURAN DAERAH KABUPATEN SEKADAU TAHUN 2019 TENTANG KETERTIBAN UMUM DAN KETENTRAMAN MASYARAKAT STUDI KASUS DI KECAMATAN SEKADAU HULU KABUPATEN SEKADAU - NIM. A1011201248, MERI ANDRIANI (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACT This thesis discusses the implementation of the provisions of boarding house business permits in Sekadau Hulu District in accordance with Sekadau Regency Regional Regulation Article 25 Paragraph (1) of Sekadau Regency Regional Regulation Number 8 of 2019 concerning Public Order and Public Tranquility (concerning study boarding house business permits in Sekadau Hulu District, Sekadau Regency). The authority of the Sekadau Regency Investment and One-Stop Integrated Service Office is one form of effort to ensure the security and order of boarding houses in Sekadau Regency. This study uses a scientific method that is descriptive analytical in nature to describe and explain the current situation and is intended to solve problems based on data and facts collected when this study was conducted. The results of the study found that many boarding houses do not have permits, all illegal boarding house owners in Sekadau Regency are aware of the existence of Regional Regulations relating to permits to own boarding house businesses, but in practice they do not comply with them by not following the rules issued in Article 25 Paragraph (1) of Sekadau Regency Regional Regulation Number 8 of 2019 concerning Public Order and Public Order, which states